Resposta da comunidade de aves ao uso do fogo nos campos de altitude do sul do Brasil - Bettio, Maurício (2017)
Grassland ecosystems compound open landscapes with predominance of grass/forb/shrub vegetation, frequently interspersed by streams, wetlands, peatbogs and forest formations. Grasslands dominate practically 40% of the terrestrial surface and they are between the more suscetible natural formations to human interventions. The highland grasslands of southern Brazil are considered natural relicts historically maintened by disturbance, as fire and herbivory. The presence of natural disturbances is an intrinsic and necessary characteristic of grasslands ecosystems, being an evolutive force that forged the landscape, selecting plants and animals, especially where the climatic and soil conditions are prone to forest development. Although fire is considered a natural disturbance into highland grasslands of southern Brazil, its regime has been altered since the arrival of humans and especially after cattle introduction, in the XVII century. In this study, we evaluate the responses of the avian community in two different situations of management of the grassland vegetation in southern Brazil: areas with annualy or biennialy burns and areas where burns were excluded/suppressed since 10-15 years ago. We dedicate two chapters to explore this subject, focusing on: (1) the avian and vegetation responses to two distinct management situations (fire vs. fire exclusion); and: (2) exploring how an accidental burning event in areas with fire exclusion for many years affected community parameters, compared to frequently burned areas. We also discuss the importance of fire disturbance to maintain a diverse avifauna and grassland ecosystems in south Brazil. We conduct samplings during the breeding season, in spring/summer 2015 to 2016. We verified that diversity of birds was not significantly different between the two management practices studied, indicating that the main effects of the frequently presence or absence of burns tend to be verifyed mainly on species composition, at least in short term. The habitat structure, measured as height of vegetation, number of woddy plants and percent of ground cover by rocks and vegetation was responsible by 80% of total variation on the composition and adundance of bird community. When we compare pre and post burn state of areas usually no burned with periodically burned areas, we verify expressive modifications, such a decrease of vegetativon height and density, a larger quantity of exposed soil into post burned areas in relation to periodically burned grasslands and the pre burned time of the usually not burned areas. Again, the avifauna differs only in relation to species composition, indicating that alteration on management dynamic is able to select bird species, benefiting or harming the occurrence of a part of community. Threatened species as Xanthopsar flavus, Anthus nattereri and Cinclodes pabsti had preference for burned grasslands with short vegetation, while Scytalopus iraiensis and Sporophila melanogaster occupied excluded grasslands where vegetation was tall and dense. Our results clearly indicate that bird communities respond significantly to different types of management employed on grassland vegetation. Studies that consider a greater temporal variation than ours, would be necessary and complementary in order to verify the resilience of grassland-specialists bird species in relation to fire events or their absence. The management with fire in grasslands has proven to be important to maintenance of birds, including globally threatened taxa. Although application of fire has legal impediments, its controlled use seems to be a strategic management tool for maintenance of bird diversity in the south brazilian highland grasslands.